The examination of the effects of obesity on a number of arteries and body mass index by using expert systems - Hardalaç, Firat; Ozan, Ahmet Tevfik; Barişçi, Necaattin; Ergün, Uçman; Serhatlio?lu, Selami; Güler, Inan (Kluwer Academic/Plenum Publishers, 2004)
In this study, the areas affected from obesity were examined by classifying divergent arteries and body mass index (BMI) of 30 healthy persons and 52 obese persons by using expert systems, and the classifying performances of NEFCLASS and CANFIS, which are expert systems were compared. As a result of this comparison, it is observed that the classifying performance of NEFCLASS is better than that of CANFIS, and the causes of this are examined. Furthermore, it is observed that after these classifications, obesity affects the BMI rather than divergent arteries.
Keywords: Arteries; Body mass index; CANFIS (coactive neuro-fuzzy inference system); NEFCLASS (neuro-fuzzy classification); Obesity data